Effect of incorporation of detoxified karanja (Pongamia pinnata) and neem (Azadirachta indica) seed cakes in total mixed rations on milk yield, composition and efficiency in crossbred dairy cows - RAJ, D N; RAMANA, J V; RAO, S B N; KUMAR, D DINESH; SURYANARAYANA, M V A N; REDDY, Y RAVINDRA; PRASAD, K S (The Indian Journal of Animal Sciences, 2016)
In the present study, neem seed cake (51.55% CP) and karanja seed cake (37.91% CP) were used as a partial replacement of soybean protein cake. Three iso-nitrogenous total mixed rations (TMR) were prepared namely T1-control where soybean meal was incorporated at 9.6% of TMR, in T -dNC and T -dKC, the cakes were incorporated at 3.85 and 5.85% of TMR and fed to eighteen crossbred cows in three groups for 90 days. Milk yield (kg/day) and FCM yield (kg/day) was found to be higher in dNC compared to dKC groups. After 90 days of feeding, both milk yield (kg/ day) and FCM yield (kg/day) increased in all the groups. The average milk fat was found to be lower in (P